Implementasi Pembelajaran PPKn dalam Pembentukan Karakter Siswa di Madrasah Ibtidaiyah Sukamanah Tanggeung Cianjur - Rahmat, Mamat; Rohmatin, Alfa; Siti Dandawiah; Elis Ashpiati; Fuji Lestari; Ai Nuni Risnawati (Jurnal Pendidikan dan Kewarganegara Indonesia, 2025)
This study aims to describe how Citizenship Education (PPKn) is implemented to shape the character of second-grade students at Madrasah Ibtidaiyah Sukamanah in Tanggeung, Cianjur. Employing a descriptive qualitative method, the research gathered data through classroom observations, interviews with teachers, and analysis of documentation related to learning activities. The findings show that PPKn learning delivered through teacher modeling, guided discussions, and consistent habitual practices effectively cultivates key character values, including discipline, honesty, responsibility, and tolerance. The integration of PPKn material with Islamic moral teachings further enhances students’ comprehension of their rights and obligations, while also reinforcing positive behavior in their daily routines. Despite these strengths, the study identifies several challenges, such as the limited availability of learning media and the diverse backgrounds of students, which influence the learning dynamics in the classroom. Overall, the results emphasize that PPKn serves as an essential foundation for character education, and its implementation needs to be continuously strengthened through innovative instructional approaches, supportive school policies, and active collaboration with students’ families to ensure optimal character development.